The Developmental direction for logistics technical manpower specialization - Kim, Jae-Moo (KDI School, 2011)
Smart weapon and equipment are determining factor to win in the future war, and thus the demand of logistics technical manpower for operating and maintaining is expected to grow. However, acquisition and development system for them in Korea Army have many problems. The acquisition system of Korea Army has focused quantitative expansion instead of qualitative improvement. As a result, a terrible minus of logistics technical manpower was easily occurred. In addition, the budget of development system for technical manpower decreased because of the sinking of the Cheo-nan ship and artillery shelling of Yeonpyeong island. Consequently, the interest for logistics technical manpower dropped. To tackle these problems, the Korea Army needs to reform the structure of technical manpower. Second, it is important that setting more practical incentives compared with private sector. Third, the opportunity of civil education regarding technical field for warrant officer and noncommissioned officer has to widen from now on. Fourth, personnel guide book for noncom has to suggest that specific standard regarding technical certification.
Thesis(Master) --KDI School:Master of Public Policy,2011